Analysis of Blood Donor Deferral in a Tertiary Care Hospital (Northern International Medical College Journal, 2020)
Introduction: Selection of proper donor according to stringent selection criteria is the prerequisite for safe blood transfusion practice. It is widely known that a large number of blood donors are deferred for different reasons.Objective: The aim of present study is to evaluate the incidence and different reasons of blood donor deferral in atertiary care hospital.Methodology: This retrospective cross-sectional study was carried out in Transfusion Medicine and Clinical Haematology Department of BIRDEM General Hospital, Dhaka, during the period from July 2016 to June 2017.The blood donor of either sex attending the mentioned department were selected purposively and categorized into four groups according to their age for this study. Donors were selected and deferred by medical officer according to national guideline. Deferred blood donors were recorded in register book and were analyzed retrospectively.Results: In current study, 1152 blood donor (8.8%) were deferred attending for allogeneic blood donation during the study period. Out of 13082 registered blood donor 11961were male (91.43%) and 1121 were female (8.57%) and deferral rate was 2.37 times more in female. Majority of the deferred donors (55.38%) were under the age of 40 where 26.82% were in between 40-49 years and 17.8% were in the range of 50 years and above. Age range of highest deferred donors (32.20%) was between 30-39 years. The number of temporary and permanent deferral were 836 (72.57 %) and 316 (27.43%) respectively. Anaemia (33.01%), underweight (21.53%) and hypotension (17.34%) were the most common reason of temporary deferral. Chronic uncontrolled hypertension (42.4%), donors with medication (16.77%) and asthma (15.18%) was the most common cause of permanent deferral.Conclusion: The deferral rate was low and most of the deferred donors were young adult. Temporary deferred donors were higher than permanent deferred donors. The most common reasons for temporary deferral were anemia, underweight and hypotension. Permanent deferral causes were chronic uncontrolled hypertension, donors on medication for various reason and asthma. Donors should be informed with a clear message on their deferral status. It is important to determine the rate and causes of donor deferral for the safety of blood transfusion and to guide the recruitment efforts for safe blood transfusion and to avoid the permanent loss of blood donors.Northern International Medical College Journal Vol.10 (2) Jan 2019: 373-376